Factors Affecting Healthcare Utilization among Patients with Single and Multiple Chronic Diseases - Ka Young KIM; Eunmi LEE; Jeonghyun CHO (Tehran University of Medical Sciences, 2020)
Background: We aimed to investigate the factors affecting healthcare utilization among patients with single and multiple chronic diseases using the Andersen healthcare utilization model. Methods: We used a combination of the data from the sixth and seventh Korea National Health and Nutrition Survey (2014-2016). The study population was 3,901 patients with single chronic disease and 1,829 patients with multiple chronic diseases as defined by the WHO. Participants were aged 19 yr or older. Multiple regression analysis was employed using the Andersen model to identify factors affecting healthcare utilization (inpatient and outpatient). Results: According to the Andersen model (comprising predisposing, enabling, and need factors and health behaviors), the factors that increased outpatients with single chronic disease were female, being aged 65 yr or older, having basic livelihood security benefit, immobility, and poor subjective health status. Factors that increased inpatients with single chronic disease were being aged under 65, having private insurance, immobility, poor subjective health status, and nondrinking. Moreover, factors that increased outpatients and inpatients with multiple chronic diseases were female, being aged under 65, immobility, and poor subjective health status and immobility, poor subjective health status, nondrinking, and not engaging in physical activity, respectively. Conclusion: We identified factors affecting outpatient and inpatient care utilization among patients with single and multiple chronic diseases, using the Andersen healthcare utilization model. The findings can be used as foundational data to develop preventive and management strategies in healthcare utilization among patients with single and multiple chronic diseases.